2020
DOI: 10.3389/fimmu.2020.575669
|View full text |Cite
|
Sign up to set email alerts
|

Dracocephalum heterophyllum (DH) Exhibits Potent Anti-Proliferative Effects on Autoreactive CD4+ T Cells and Ameliorates the Development of Experimental Autoimmune Uveitis

Abstract: Experimental autoimmune uveitis (EAU) is a CD4 + T cell-mediated organ-specific autoimmune disease and has been considered as a model of human autoimmune uveitis. Dracocephalum heterophyllum (DH) is a Chinese herbal medicine used in treating hepatitis. DH suppressed the production of inflammatory cytokines through the recruitment of myeloid-derived suppressor cells (MDSCs) to the liver. However, it remains elusive whether DH can directly regulate CD4 + T cell biology and hence ameliorates the development of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Dilution of eFluor-670 was analyzed by flow cytometry. For in vitro Treg suppression of dendritic cell activation, bone marrow-derived dendritic cells (BMDCs) were generated from femoral and tibial bones cells as previously described ( 30 ). BMDCs (0.5×10 5 /well) were either cultured alone or mixed with sorted Treg cells at a ratio of 1:1 and seeded in 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Dilution of eFluor-670 was analyzed by flow cytometry. For in vitro Treg suppression of dendritic cell activation, bone marrow-derived dendritic cells (BMDCs) were generated from femoral and tibial bones cells as previously described ( 30 ). BMDCs (0.5×10 5 /well) were either cultured alone or mixed with sorted Treg cells at a ratio of 1:1 and seeded in 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin [137,138] Dracocephalum heterophyllum Benth. Rosmarinate, luteolin, and diosmetin [139,140] Dracocephalum kotschyi Boiss. Apigenin [141] Dracocephalum moldavica L. Tilianin, dracocephalumoid A, uncinatone, trichotomone F, and caryopterisoid C [107,108] Dracocephalum palmatum Stephan ex Willd.…”
Section: Species Secondary Metabolites With Anti-inflammatory Activit...mentioning
confidence: 99%
“…It has been used in Tibetan medicine for the treatment of various diseases such as jaundice, liver disease, lymphangitis, mouth ulcers, and dental disease [ 1 ]. A number of prior reports have indicated that it also has antioxidant activity [ 2 , 3 ], anti-diabetic activity [ 4 ], inhibits hepatitis, and improves autoimmune diseases [ 5 ]. In addition, previous studies related to the analyses of phytochemical constituents have revealed that different flavonoids, alkaloids, triterpenes, and phenylpropanoids could be isolated from D. heterophyllum , but the chemical constituents currently obtained from D. heterophyllum are limited, which are not enough to support the subsequently reported pharmacological activities and pharmacodynamics mechanism research.…”
Section: Introductionmentioning
confidence: 99%